2020
DOI: 10.1016/j.sigpro.2019.107246
|View full text |Cite
|
Sign up to set email alerts
|

Distributed multi-sensor multi-view fusion based on generalized covariance intersection

Abstract: Distributed multi-target tracking (DMTT) is addressed for sensors having different fields of view (FoVs). The proposed approach is based on the idea of fusing the posterior Probability Hypotheses Densities (PHDs) generated by the sensors on the basis of the local measurements. An efficient and robust distributed fusion algorithm combining the Generalized Covariance Intersection (GCI) rule with a suitable Clustering Algorithm (CA) is proposed. The CA is used to decompose each posterior PHD into well-separated c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 56 publications
(88 reference statements)
0
24
0
Order By: Relevance
“…On the other hand, AA is more suitable for higher rates of missed detections since it tends to preserve all the detected objects. Taking into account these characteristics, it is clear that GCI fusion is hard to combine with sensors that have limited FoVs [27], [28], because the limited FoVs increase the chances of misdetected objects. For this reason, we choose to use AA.…”
Section: B Map Fusion At the Bsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, AA is more suitable for higher rates of missed detections since it tends to preserve all the detected objects. Taking into account these characteristics, it is clear that GCI fusion is hard to combine with sensors that have limited FoVs [27], [28], because the limited FoVs increase the chances of misdetected objects. For this reason, we choose to use AA.…”
Section: B Map Fusion At the Bsmentioning
confidence: 99%
“…Notice that such a region includes the accumulated FoV F k|k (x, m) refer to X k , the PHD D BS k|k−1 (x, m) refers to X k , and finally the PHD D (n) k|k (x, m) refers to X k . Given the decompositions in (28) and (29), the fused PHD is then computed as…”
Section: B Map Fusion At the Bsmentioning
confidence: 99%
See 1 more Smart Citation
“…One solution is to extend the prior FoVs of all sensors to an identical and larger FoV before fusion (Battistelli et al, 2017;Li SQ et al, 2018), but this may underestimate the existence probabilities of targets in non-public areas. Another widely used method is to split the information according to the FoVs' intersection (Gan et al, 2016;Vasic et al, 2016;Li TC et al, 2019c;Da et al, 2020b;Li GC et al, 2020). Fusion will be executed in each splitting area separately, followed by a reunion operation for all areas.…”
Section: Limited Fields Of Viewmentioning
confidence: 99%
“…Li et al [9] took the target and image data as experimental inputs, and observed that not all regions of the image or target are key effective information for cross modal mapping in the generalization problem. Li et al [10] pioneered the application of zero-shot learning (ZSL) and cross domain hash to SBIR, and greatly expanded the research scope of ZS-SBIR. Experimental results show that Li's method only achieved a 1% higher map than traditional methods, but the introduction of the heterogeneous network is a breakthrough.…”
Section: Introductionmentioning
confidence: 99%